Intelligence agencies release exploit details. Issue 8 (August 2021) - Unknown
Abstract : The vulnerabilities most commonly exploited by nation-state attackers – most notably, China, Iran and Russia – are detailed in a new advisory jointly issued by government agencies in the US, UK and Australia.